Взаємодія реального та фантастичного світів в оповіданнях Федора Сологуба - Мацієвська, В. (Літературознавчі обрії. Праці молодих учених, 2010)
Symbolism is one of the art movements of modernism which has arisen on the boundary of XIX and XX centuries. It was most fully developed in France and Russia. Interaction of the real and unreal worlds is one of the typical lines of symbolism which is brightly presented in the stories of Russian symbolist writer F. Sologub.